Prevalence of Wasting, Thinness, Stunting and Under-weight among Paediatric AIDS Patients in a Tertiary Centre - Anyanwu, Onyinye Uchenna; Onyire, Benson Nnamdi; Daniyan, Faith W. (Journal of Nepal Paediatric Society, 2016)
Introduction: Malnutrition is a common occurrence in HIV positive children. Its presence reflects the level of care the child receives as well as affects the outcome of their infection. The objective of this study was to determine the prevalence of various forms of malnutrition among HIV positive children. This was a Hospital based Cross-sectional study in HIV-positive children receiving care in FETHA. Material and Methods: using the WHO reference standards, we determined the prevalence of wasting, thinness, stunting and underweight in HIV-positive children receiving care in FETHA. Height and weight measurements of 89 HIV-positive children aged 0-18year old were taken. Socioeconomic stratification was done by Olusanya’s criteria. Results: The prevalence of wasting, thinness, stunting and underweight in HIV- positive children were 31(34.8%), 22(24.7%), 30(33.7%), and 33(37.1%) respectively. Age group and socioeconomic status were significantly associated with the various forms of malnutrition while gender and clinical stage of disease were not. Conclusion: There is still a high prevalence of acute and chronic malnutrition amongst paediatric-AIDS patients which is significantly more amongst adolescents and the lower socioeconomic class. J Nepal Paediatr Soc 2016;36(2):156-159.